Excitons in Nanosystems Consisting of Semiconductor Quantum Dots - Pokutnyi, S.I.; Gorbyk, P.P.; Makhno, S.M.; Prokopenko, S.L.; Mazurenko, R.V. (Наносистеми, наноматеріали, нанотехнології, 2017)
As found, within the band gap of the quantum dot of zinc selenide, a zone of exciton states located at the bottom of the conduction band appears. As shown, a decrease in the band gap width for this nanosystem is conditioned by transition of the electron from quantum-dimensional level within the valence band of the quantum dot to the levels of the zone of exciton states. The dependence of the energy of a ground state of an exciton on the radius of quantum dot is obtained using a modified method of the effective mass.